Efficacy of Desloratadine Treatment of Children with Allergic Rhinitis - R. M. Faizullina; Ye. D. Guseva (Вопросы современной педиатрии)
The article describes the results of the treatment of children aged 7–15 with allergic rhinitis during the acute phase of the disease. It compares the clinical efficacy of desloratadine monotherapy in children with intermittent seasonal allergic rhinitis, persistent allergic rhinitis, and persistent allergic rhinitis with non-acute asthma. It was found that the immunoglobulin concentration in nasal secretions changes when treating children with seasonal allergic rhinitis. The results obtained can be used in assigning patients with allergic rhinitis to treatment.